Hearing, Reflection, and Cultivation: Relating the Three Types of Wisdom to Mindfulness - Anālayo, Bhikkhu (Religions, 2021)
A text-historical perspective on the Buddhist scheme of three types of wisdom, acquired by hearing, reflection, and cultivation, shows that a bare listing in the earliest textual strata has led to somewhat differing perspectives in later exegesis of the Theravāda and Sarvāstivāda traditions, the former apparently being influenced by what appears to be an error in oral transmission. The more convincing position taken in Sarvāstivāda exegesis sees these three types of wisdom as interrelated activities that can rely on mindfulness, thereby testifying to the flexibility and broad compass of mindfulness in Buddhist thought as something not limited to a rigid division between theory and practice.